Marian Rusecki’s Axiological Argumentation for the Credibility of Christianity and the Church - Mastej, Jacenty (Studia Warmińskie, 2024)
The aim of this project is to present the axiological argumentation for the credibility of Christianity and the Church, contained in the scientific work of Fr prof. Marian Rusecki. The implementation of the undertaken task begins with a discussion of axiological principles. Then, the values to which the theologian refers in building axiological argumentation are dealt with: the dignity of the human person, truth, goodness, love and holiness. For the professor, Christianity is the value of the highest importance, because it is the carrier of revealed values, unites them in itself and realises them in a saving way. The theological and fundamental argumentation built by M. Rusecki is about showing that Christianity, faith in Jesus Christ, is an absolutely unique value for man, because it gives him the highest good: God and salvation. Rusecki’s axiological argumentation for the credibility of Christianity and the Church is of a personalistic nature. In building an axiological argument, the professor from Lublin refers to the category of a sign, which has two elements: visible and invisible. He considers their complex structure: natural and supernatural to be a specific feature of Christian values. Therefore, full axiological diagnosis requires the participation of reason and faith. The highest value in Christianity is Jesus Christ, the Incarnate Son of God. He is a personal and absolute value, because in Him the completeness and personal realisation of the dignity of the human person, truth, goodness, love and holiness are shown.